Old Truths and New Clichés : Essays by Isaac Bashevis Singer - Singer, Isaac Bashevis, 1904-1991 (Book collections on Project MUSE., 2022)
From the Nobel Prize-winning writer, a new collection of literary and personal essaysOld Truths and New Clichés collects eighteen essays--most of them previously unpublished in English--by Isaac Bashevis Singer on topics that were central to his artistic vision throughout an astonishing and prolific literary career spanning more than six decades. Expanding on themes reflected in his best-known work--including the literary arts, Yiddish and Jewish life, and mysticism and philosophy--the book illuminates in new ways the rich intellectual, aesthetic, religious, and biographical background of Singer's singular achievement as the first Yiddish-language author to be awarded the Nobel Prize for Literature.Like a modern Montaigne, Singer studied human nature and created a body of work that contributed to a deeper understanding of the human spirit. Much of his philosophical thought was funneled into his stories. Yet these essays, which Singer himself translated into English or oversaw the translation of, present his ideas in a new way, as universal reflections on the role of the artist in modern society. The unpublished essays featured here include "Old Truths and New Clichés," "The Kabbalah and Modern Times," and "A Trip to the Circus."Old Truths and New Clichés brims with stunning archival finds that will make a significant impact on how readers understand Singer and his work. Singer's critical essays have long been overlooked because he has been thought of almost exclusively as a storyteller. This book offers an important correction to the record by further establishing Singer as a formidable intellectual.